Peran Moderasi Persaingan Pada Pengaruh Modal Terhadap Risiko Kegagalan Bank - Fuad, Ahmad; Disman, Disman; Nugraha, Nugraha; Mayasari, Mayasari (Program Studi Akuntansi FPEB UPI, 2021)
Abstract. This study aims to examine the moderating role of bank competition proxied by the lerner index on the effect of bank capital on bank failure risk proxied by the Z-score. This test considers control variables from bank-specific factors such as Return on Assets (ROA), Loan to Deposit Ratio (LDR), and Non-Performance Loans (NPL) as well as macroeconomic factors such as Gross Domestic Product (GDP), inflation, and Bank Indonesia interest rates. The sampling technique used was purposive sampling. The data sample obtained was 96 banks from a population of 114 banks which consistently operated during the period 2008-2018. Hypothesis testing using panel data regression analysis techniques through the first model of Hayes method. The results showed that competition at various levels (low, medium, high) positively moderated (strengthened) the inverse of capital on the risk of bank failure. This finding is consistent with the view that competition encourages banks to increase their the level of capital. This study does not include bank efficiency factors and is limited to conventional banks only, further researchers can use the results of this study as a reference or study material, and even re-research objects by adding these factors.